Visible Light Photocatalytic Decolourization of Methyl Orange Using N-Doped TiO2 Nanoparticles - Hadi, Hussein M; Wahab, Hilal S (Al-Nahrain Journal of Science, 2015)
In the present study, nitrogen doped TiO2 (N-TiO2) has been synthesized by simple sol-gel technique. The light absorption property and morphology of the N-TiO2 were characterized by Diffused Reflectance UV-VIS spectrometer and scanning electron microscopy (SEM). The results showed a clear shift in the light absorption from UV region (380) to visible region (410 nm). SEM results showed the morphology was changed after doping process compared with the pure anatase TiO2. The photocatalytic activity was examined by the photo decolorization of the Methyl Orange which was used as a pollutant model in this study under visible light irradiation. The main operational parameters, namely, initial pollutant concentration, doped photocatalyst loading, pH of photocatalysis solution and visible light intensity on the rate of photocatalytic decolorization. The results show that N doping induced the enhancement of photocatalytic decolorization. Methyl orange removal efficiency results at optimum experimental conditions have revealed more than 98% degradation after 60 minutes of illumination.